Tratamento de feridas crônicas com oleorresina de copaíba. - Viviane Vasconcelos Leite (2022)
The World Health Organization has expressed itself on the need to evaluate the effective and safe use of medicinal plants, given that a large part of the population uses plants or their preparations in everyday life. In this context, the use of phytotherapy in the treatment of wounds stands out, from antiquity to the present day. In the city of Betim (Minas Gerais/Brazil), the practice of phytotherapy has been consolidated through the Farmácia Viva Program, since 2004. Among the preparations dispensed in the program are sunflower oil + copaíba 7% and copaiba cream at 10 % used in wound care. Thus, the aim of the present study was to evaluate the efficacy and effectiveness of copaiba oleoresin in the treatment of wounds. The research was developed in three stages: initially a theoretical study, with literature review, then pre-clinical studies and finally a clinical study of the case series type. The thesis was presented in the form of articles, with three complementary articles being developed. In the literature review on the traditional use of medicinal plants for the treatment of wounds, which included Copaifera spp., information obtained from the databases of journals with ethnobotanical publications and from the bibliographic collection of the Center Specialized in Aromatic, Medicinal and Toxic Plants was analyzed. from the Federal University of Minas Gerais. In the second stage, the characterization of copaiba oleoresin and sunflower oil was carried out. The ideal concentration of preparations with copaiba oleoresin, its action on fibroblast proliferation, cytotoxicity test and microbial inhibition were also studied. These results are presented in the first and second articles. The last step was presented in the third article, in which the effectiveness of copaiba oleoresin in the treatment of chronic wounds in patients from the health care network of Betim was evaluated, through a retrospective observational study. The reference preparations were: “10% copaiba cream” or “sunflower oil + 7% copaiba oleoresin”, and the data were collected from the Farmácia Viva Program database, and by surveying the clinical evolutions in the medical records. of patients. The results of the literature review highlight copaiba as one of the Brazilian medicinal plants that remain the object of study among researchers today, demonstrating new evidence of its effectiveness in wound healing, however with few studies of effectiveness in humans. The second study observed that the concentration of 10% of copaiba oleoresin in sunflower oil had the greatest effect on cell growth. However, the greatest microbial inhibition occurred with pure oleoresin. Finally, the effectiveness study showed that preparations with copaiba used in Betim accelerated the healing process of chronic wounds, facilitating the formation of epithelial tissue in a short period of time. This thesis concludes that the beneficial effects recorded in the historical data reflect the healing, antimicrobial and anti-inflammatory properties of copaiba oleoresin, with action in the healing process of chronic wounds.